(untitled) (Research, Society and Development, 2022)
Social isolation in childhood has several consequences from low social interaction to impaired growth and development, so this work aims to bring these effects to the various aspects of child development today. This will be done through the characterization of the experiences that are placed around them, leading to cognitive development, quick thinking, communication, languages, motor and social skills. An integrative literature review was carried out in an electronic database of SciELO and PubMed done accordingly to DeCS, through inclusion and exclusion criterias for the selection scientific works, associated with complementary database from FIOCRUZ and Ministério da Saúde. Furthermore, for the development of the first stage of the project, the PICO method was used. Through this work, the importance of the environment in which the individual is inserted is exposed, showing that the lack of social interaction through isolation will damage their development. As well as showing the importance of understanding the process of human development and its two main stages, the social and the emotional, to deal better with problems that may appear in early childhood. It is concluded that child isolation would bring harm in adult life and delays in child development. In adult life, it causes difficulties in academic achievements, greater chance of neural, biological, psychiatric, socioeconomic and educational damage. The delay in childhood would be directed towards motor, intellectual, linguistic and psycho-emotional skills.